Beneficiation of Iron-Copper Ores from Kasaan Peninsula, Prince of Wales Island, Alaska - Wells, R. R.; Erspamer, E. G.; Sterling, F. T. (United States. Bureau of Mines., 1957)
Report issued by the Bureau of Mines over studies conducted on the beneficiation of iron-copper ores. As stated in the summary, "this report summarizes the results of laboratory testing of copper-bearing magnetite ore from the Poorman, Rush and Brown, and Copper Center deposits, Kasaan Peninsula, Prince of Wales Island, southeastern Alaska" (p. 1). This report includes tables, maps, and illustrations.